Environmentally Friendly Household Organic Waste Treatment For The Community Of Majelis Taklim Annisa Swadaya-89 Gunung Terang Bandar Lampung - Rochmah Agustrina; Gina Dania Pratami; Dzul Fithria Mumtazah; Eti Ernawiati (CV. Multi Kreasi Media, 2025)
Household organic waste is all organic waste generated at home from daily activities. Household organic waste has been a problem because it causes unpleasant odors if it decomposes and is not treated, its presence left unattended in the home environment also triggers the growth of microorganisms and insects such as flies. Household waste comes from various sources, especially food waste, unnecessary purchases. Household waste can cause illness, air pollution and environmental contamination. Household waste treatment options include landfill, burning for energy, recycling, and composting. This community service activity aims to introduce organic household waste composting methods to the congregation of majelis taklim Annisa Swadaya-89, Gunung Terang, Bandar Lampung through the method of making eco-enzyme, making compost with the help of composting microbes, and introducing composting with maggot, so that people are familiar with composting and recycling activities. The results showed an increase in the participants' knowledge level as measured by the pre-test and post-test. The participants' knowledge increased by 32% from the average final score of the respondents. The positive results of this service activity can be used by the community as a basis for changing household waste treatment patterns, so that waste is no longer a problem that reduces the quality of household environmental health of the congregation of Majelis Taklim Annisa Swadaya-89 Gunung Terang.